Pelatihan Penggunaan Aplikasi Program Pemasaran Bersama (ePPB) dalam Rangka Meningkatkan Fleksibilitas Pemasaran Industri Mikro dan Kecil di Kota Surabaya - Wahyudiono Wahyudiono; Santirianingrum Soebandhi; Dana Aditya; Luthfia Nabila Hidayani (Kolaborasi : Jurnal Hasil Kegiatan Kolaborasi Pengabdian Masyarakat, 2026)
This community service aims to provide training on the use of the Joint Marketing Program (eJMP) application module to micro and small industry players in the Surabaya city, so that marketing of MSI products can be carried out flexibly without being limited by space, place and time, so that marketing can reach a wider network and ensure the sustainability of MSI businesses in the future. This community service activity uses a qualitative descriptive approach by photographing the real conditions of marketing management of micro and small industries, then providing eJMP module training to 20 micro and small industry sector players as well as owners who are domiciled in the Surabaya city. The eJMP module training method is implemented through four stages, namely: (1) identifying the suitability of the eJMP module content to the marketing needs of MSI businesses, (2) determining the eJMP module training model with its marketing literacy priorities, (3) elaborating the eJMP content with MSI marketing literacy materials, and (4) implementing the eJMP module training for micro and small industry players. The results of this training indicate that micro and small industry players still experience difficulties in marketing MSI products, therefore optimizing the use of the eJMP application can help micro and small industry businesses to optimize marketing together, flexibly and effectively. This eJMP application module training includes material on the important role of joint marketing, optimizing the role of cooperatives, an introduction to the eJMP application and joint marketing simulations through the eJMP application. This training, which is carried out in a structured and systematic manner for micro and small industry players, is expected to be able to improve flexible and effective joint marketing and ensure the sustainability of MSI businesses in the future .